Patulibacter medicamentivorans sp nov., isolated from activated sludge of a wastewater treatment plant - Bárbara Almeida (2013)
A Gram-positive, aerobic, non-motile, non-endospore-forming rod-shaped bacterium with ibuprofen-degrading capacity, designated strain I11(T), was isolated from activated sludge from a wastewater treatment plant. The major respiratory quinone was demethylmenaquinone DMK-7, C-18:1 cis9 was the predominant fatty acid, phosphatidylglycerol was the predominant polar lipid, the cell wall contained meso-diaminopimelic acid as the diagnostic diamino acid and the G+C content of the genonnic DNA was 74.1 mol%. On the basis of 16S rRNA gene sequence analysis, the closest phylogenetic neighbours of strain I11(T) were Patulibacter ginsengiterrae CECT 7603(T) (96.8% similarity), Patulibacter minatonensis DSM 18081(T) (96.6 %) and Patulibacter americanus DSM 16676(T) (96.6%). Phenotypic characterization supports the inclusion of strain I11(T) within the genus Patulibacter (phylum Actinobacteria). However, distinctive features and 16S rRNA gene sequence analysis suggest that is represents a novel species, for which the name Patulibacter medicamentivorans sp. nov. is proposed. The type strain is I11(T) (=DSM 25962(T)=CECT 8141(T)).